ANALISIS PENDAPATAN ASLI DAERAH, DANA BAGI HASIL, DAN JUMLAH PENDUDUK TERHADAP BELANJA DAERAH DI PROVINSI SUMATERA BARAT - Mia Fajriati; Zulfatunnisa Zulfatunnisa; Dinar Rifatul Wafa; Rika Amanda Heryaningrum; Saiful Anwar (P3M STISIPOL Dharma Wacana Metro, 2021)
Regional spending aims to prosper the community and advance the region, when regional income increases, the region will be more capable and independent to finance regional expenditures. This study aims to determine the effect of Regional Original Income, Revenue Sharing Funds and Total Population on Regional Expenditures. The population of this study is the Regency and City in West Sumatra Province. The sampling methode uses quantitative methods with analytical techniques in the form of panel data regression analysis. The results of this study indicate that the Regional Original Revenue has a significant positive effect on Regional Expenditure, while the Revenue Sharing Fund has a positive and significant effect, and the Number of Population has an insignificant negative effect. It is hoped that this research can be a reference in further research. It is hoped that this research can be a reference for the government to better utilize existing resources in order to prosper the community and better optimize the use of local revenue, regional expenditure funds, and profit-sharing funds.